2012
DOI: 10.3892/ol.2012.1006
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism array analysis of microsatellite-stable, diploid/near-diploid colorectal carcinomas without the CpG island methylator phenotype

Abstract: Abstract. Colorectal carcinomas are considered to progress by chromosomal instability (CIN), or microsatellite instability (MSI) and/or epigenetic gene silencing; however, in previous studies we observed a small fraction of tumours without this molecular phenotype. To further investigate these 'X-type' tumours, neoplastic glands from five tumours were isolated by laser-capture microdissection and used for single nucleotide polymorphism (SNP) array analyses. DNA from our own lowpassage primary colorectal carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Although BCL2 is not usually considered to be a tumor suppressor gene, it has been reported to act as one under certain circumstances [ 61 ]. Furthermore, one of the frequently deleted regions contained MACROD2 at 20p12.1 which was also described in a recently published study by Linnebacher et al [ 62 ].…”
Section: Discussionsupporting
confidence: 75%
“…Although BCL2 is not usually considered to be a tumor suppressor gene, it has been reported to act as one under certain circumstances [ 61 ]. Furthermore, one of the frequently deleted regions contained MACROD2 at 20p12.1 which was also described in a recently published study by Linnebacher et al [ 62 ].…”
Section: Discussionsupporting
confidence: 75%
“…Exon 5 of MACROD2 gene was originally found disrupted in Japanese children affected by the Kabuki syndrome, a rare, clinically congenital mental retardation syndrome of unknown etiology, characterized by facial anomalies and mental retardation (Maas et al, 2007; Kuniba et al, 2008). Deletions or SNPs in the gene locus of MACROD2 have been often associated with tumor progression, neurological and psychiatric disorders (Anney et al, 2010; Lionel et al, 2011; Perlis et al, 2012; Cheng et al, 2013; Jahanshad et al, 2013; Linnebacher et al, 2013; Tsang et al, 2013; Jones et al, 2014; Mohseni et al, 2014; Briffa et al, 2015; van den Broek et al, 2015; Hu et al, 2016; Sakthianandeswaren et al, 2018). However, in the case of neurological and psychiatric disorders, such as for autism spectrum disorder (ASD) or for attention deficit hyperactive disorder (ADHD), the MACROD2 association failed to replicate in well-powered cohorts (Bradley et al, 2010; Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MACROD2 is of one of the tree monoADP-ribosylases (MARs) in humans, together with macroD1 and C6orf130, which possesses reversible ADP-ribosyl hydrolase activity and is required for its recruitment to DNA lesions induced by laser microirradiation (Jankevicius et al, 2013; Rosenthal et al, 2013; Barkauskaite et al, 2015). Abnormalities in the sequence of the gene locus of MACROD2, most often deletions or single nucleotide polymorphisms (SNPs), have been consistently associated with cancers, neurological and psychiatric disorders (Anney et al, 2010; Lionel et al, 2011; Perlis et al, 2012; Cheng et al, 2013; Jahanshad et al, 2013; Linnebacher et al, 2013; Tsang et al, 2013; Jones et al, 2014; Mohseni et al, 2014; Briffa et al, 2015; van den Broek et al, 2015; Hu et al, 2016; Sakthianandeswaren et al, 2018). Beyond the in vitro and clinical association studies discussed above, the in vivo function and the exact molecular functions of MACROD2 are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, apparently the majority of so-called PTEN LOHs reported in the literature 'ever since Knudson' (5) may well be spurious and not play a role functionally, particularly not as one of the 'hits' of a tumour-suppressor gene mechanism involving the PTEN gene. The reason for AI is well explained when taking into account the results from a different methodological approach; some of our xenotransplants have previously been analyzed by single-nucleotide polymorphism (SNP)-arrays [ HROCs 18,32,39,40,46,59,60,80; published in (16)]. These investigations showed that the AI is in fact the result of unbalanced large-scale genomic amplification (trisomy 10 or p-arm amplification).…”
Section: Discussionmentioning
confidence: 99%